Second-generation immigrant Indian's identity formation: An intersectional study of pan-ethnicity, gender, and religion - Saheeh Shafi (Indonesian Journal of Social Sciences, 2023)
This paper explores the multi-dimensional Asian American identity of immigrant Indians from their interview responses. Pan-ethnic identity of Indians in the US as Asian Americans, the Mar Thoma Church community for religious identity, and the second-generation Patel family’s union formation in terms of gender identity will be analyzed to find out the reasons behind their choice of a particular identity. Historical frameworks like Asian American movement and theoretical frameworks like identity formation theories will be used to interpret the reasons behind the choice of the identity of Indian Americans. For analyzing interview data, methodological frameworks, including thematic and statistical analysis, will be used. Results show the reasons behind their choice of different identities, including professional advantage and their future directives as part of hypotheses of Indian Americans as they merge with the American identity as part of cultural assimilation, in other cases, retain their Asian-ness beyond Americanized identity and sometimes go beyond both American, Asian identity to restate their Indian ethnicity. To conclude, the identity of Indian Americans remains evenly poised and keeps on changing due to the requirements of the ever-evolving world.